Analysis of the Effectiveness of the Execution of Mortgage Rights from the Perspective of the Principle of Good Faith and Balance of Interests - Ismed, Ismed; Fitri Rafianti; Henry Aspan (PT. Sinergi Legal Publisher, 2025)
Parate execution of mortgage rights is a legal instrument that grants extraordinary authority to creditors to auction collateral objects without going through the courts, as stipulated in Article 6 and Article 14 paragraph (2) of Law Number 4 of 1996 concerning Mortgage Rights. This mechanism is normatively claimed as a form of efficiency and legal certainty in resolving problem loans. However, in practice, the implementation of parate execution is fraught with inequality and potential violations of the principle of justice, especially for debtors. Many debtors are forced to lose assets through public auctions conducted unilaterally, without room for negotiation, without adequate supervision, even at auction prices that do not reflect fair market value. As a result, instead of settling their debts, debtors are trapped in the trap of remaining debt after execution. This proves that the law has been used to perpetuate the economic domination of creditors and ignore the basic rights of debtors. This research shows that the concept of parate execution in the UUHT does not fully reflect the principles of good faith and balance of interests as mandated in Article 1338 paragraph (3) of the Civil Code and the decisions of the Constitutional Court. The imbalance in bargaining position between creditors and debtors is not compensated by adequate legal protection. Therefore, it is necessary to reformulate the norms, including limiting the right of unilateral execution, strengthening the space for negotiation, and developing alternative auction mechanisms that are fairer and more transparent. Without fundamental corrections, parate execution will continue to be a tool for legalizing structural inequalities that harm social justice and negate the spirit of the law as a guardian of the human rights of every citizen.